Inside Front Cover: MALDI imaging mass spectrometry of Pacific White Shrimp L. vannamei and identification of abdominal muscle proteins. Issue 11 (15th June 2016) - Schey, Kevin L.; Hachey, Amanda J.; Rose, Kristie L.; Grey, Angus C.
Abstract : DOI:10.1002/pmic.201500531 Imaging mass spectrometry reveales tissue specific protein localization in Pacific white shrimp. Tissue microextraction is combined with top‐down proteomics to identify novel abdominal muscle proteins. Sequence tags identified from electron transfer dissociation (ETD) spectra are searched against an EST database to identify nucleotide sequences that are then translated to the predicted protein sequence. Final proteoform assignment is accomplished by matching ETD fragments to the modified protein sequence. For details, see research article by Kevin L. Schey et al., on page 1767.